Social Development in Pakistan : Annual Review 2000 - Published by Oxford University Press (Karachi, Pakistan Oxford University Press, 2001)
This text examines "Towards Poverty Reduction", SPDC's third annual review of social development in Pakistan, which proposes a three-pronged comprehensive poverty reduction strategy focusing on greater opportunity, empowerment, and welfare.
Include Tables, Colour Illustration, Appendix and Bibliography
Keywords: Social conditions -- Economic history